Experimental and numerical analysis of heat distribution for different joining metal of tailor welded process - Mohd Naqiuddin, Mohd Salleh (2013)
Tailor welded blank (TWB) is commonly used in industrial. Tailor welded blanks are defined as two or more separate pieces of flat material, dissimilar thickness, and or mechanical properties. This project aim to do experiment and numerical analysis of heat distribution in TWB process of different material with the same thickness. Heat is major parameter in TWB process. Hence, it must be optimized for the process. Among the considered factors are to minimize heating width and use high intensity heat flux to generate enough heating energy inside the work-piece. This project concentrates on heat transfer characteristic for the common used type of TWB material. Actual heat distribution will be measured in experiment by using DASYLab software and will be used to validate FE model. This project must focusing on fabricate simple heat transfer testing equipment and develop equivalent finite element of heat transfer test. It also focuses on developing finite model for static heat source case of TWB process. Abaqus software has been used to simulate the heat transfer in the case of joining the dissimilar materials. After the result is validated, the parametric study to get the best position of heat source. The result shows the heating source must be far away as possible from the low melting point. For simulation, case 1, the joining aluminium and mild steel, the heating source must be placed at a location where 40% in aluminium and 60% in mild steel. In case 2, the joining is stainless steel and mild steel, the position of heating source must be placed in the middle, 50% in mild steel and 50% in stainless steel. The last case, the joining aluminium and stainless steel, the position of heating source must be placed 40& in stainless steel and 60% in aluminium. The completed joining with dissimilar material that can reduced the final car weight and can improved fuel economy.